Motivation, Work Culture, Commitment, and Leadership Style on Job Satisfaction and Employee Performance in Pekerjaan Umum dan Penataan Ruang (PUPR) Services in Kampar District - Bakhroini; Achmad Tavip Junaedi; Rizaldi Putra (Institut Bisnis dan Teknologi Pelita Indonesia, 2022)
This research aims to examine and analyze the effect of motivation, work culture, commitment, and leadership style on job satisfaction and employee performance at the Pekerjaan Umum dan Penataan Ruang (PUPR) Department of Kampar Regency. Data collection techniques are interviews, questionnaires, and employee data. The population in the research is 120 employees and the method used in determining the number of samples in this study was the total sample method using census techniques so that the number of samples was as much as 120 respondents. Analysis using Structural Equation Modeling (SEM). Results showed that motivation has no effect on job satisfaction, work culture has no effect on job satisfaction, commitment has an effect on job satisfaction, leadership style has no effect on job satisfaction, motivation has an effect on employee performance, work culture has no effect on employee performance, commitment has to effect on employee performance, leadership style has an effect on employee performance and job satisfaction has an effect on employee performance.